A Comparative Analysis of The Linguacultural Features of The Concepts "Nation" And "Individual" (Based on English and Uzbek Languages) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This paper presents a comparative linguacultural analysis of the foundational concept’s "nation" (nation / millat) and "individual" (individual, personality / shaxs) within the English and Uzbek linguistic worldviews. The relevance of this study stems from the necessity to examine the mental constants of structurally diverse languages in the context of intercultural communication. The methodology relies on conceptual and definitional analysis, alongside the linguistic description of frame structures. As a result of the research, the authors explicate both universal (isomorphic) and ethno-specific (differential) semes. It is established that the English linguaculture demonstrates a pronounced egocentric (individualistic) dominant, where the concept of the "individual" takes precedence over supra-individual structures. Conversely, in the Uzbek linguistic worldview, the concepts of "nation" and "individual" exist in a relationship of synergetic paternalism, wherein the value of the individual is actualized through service to the community
Keywords: linguacultural studies; comparative linguistics; contrastive linguistics